2010
DOI: 10.1039/b925672e
|View full text |Cite
|
Sign up to set email alerts
|

Dynamic mean field theory of condensation and evaporation processes for fluids in porous materials: Application to partial drying and drying

Abstract: We study the dynamics of evaporation for lattice gas models of fluids in porous materials using a recently developed dynamic mean field theory. The theory yields a description of the dynamics that is consistent with the mean field theory of the thermodynamics at equilibrium. The nucleation processes associated with phase changes in the pore are emergent features of the dynamics. Our focus is on situations where there is partial drying or drying in the system, associated with weakly attractive or repulsive inte… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
32
0

Year Published

2011
2011
2022
2022

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 23 publications
(34 citation statements)
references
References 43 publications
2
32
0
Order By: Relevance
“…[24][25][26][30][31][32][33][34] The theory provides a mean field approximation to the master equation for the dynamics of a lattice gas 1 2 3 4 5 6 7 8 9 10 11 12 13 14 15 16 17 18 19 20 21 22 23 24 25 26 27 28 29 30 31 32 33 34 35 36 37 38 39 40 41 42 43 44 45 46 47 48 49 50 51 52 53 54 55 56 57 58 59 …”
Section: Model and Theorymentioning
confidence: 99%
See 1 more Smart Citation
“…[24][25][26][30][31][32][33][34] The theory provides a mean field approximation to the master equation for the dynamics of a lattice gas 1 2 3 4 5 6 7 8 9 10 11 12 13 14 15 16 17 18 19 20 21 22 23 24 25 26 27 28 29 30 31 32 33 34 35 36 37 38 39 40 41 42 43 44 45 46 47 48 49 50 51 52 53 54 55 56 57 58 59 …”
Section: Model and Theorymentioning
confidence: 99%
“…Several applications of the theory have been published in recent years. [25][26][27][28][29] In a recent paper we applied DMFT to the case of the filling of closed end pores and were able to identify two dynamic regimes depending on the pore length. 30 In this paper we build on that work by applying DMFT to the study of some of the pore geometries found in the TEM studies of Psi, specifically ink bottle structures and side stream pores, as well as to long chains of such pore geometries.…”
Section: Introductionmentioning
confidence: 99%
“…We can consider higher order approximations beyond the mean field approximation using the path probability method [58]. Our work on this so far indicates that the qualitative picture is unchanged by going to the higher order theory [35].…”
Section: Discussionmentioning
confidence: 97%
“…Implementation of DMFT involves a numerical solution of Eq. (6) and Euler's method [27,35] is typically used. More implementation details are described in [27, 34 -36].…”
Section: Dynamic Mean Field Theorymentioning
confidence: 99%
“…Since then, there have been numerous refinements and applications of the DDFT methods for both continuous and discrete systems, ranging from spinodal decomposition to molecular diffusion, wetting, condensation-evaporation, imbibition-drainage, etc. 5,[7][8][9][10][11][12] Based on its formal derivation, the DDFT method describes the relaxation of Brownian particles in a medium, with two important approximations: (a) the adiabatic approximation and (b) that the local velocity distribution is close to the Maxwellian. 13 The former assumption implies that one can approximate the spatial correlations in the non-equilibrium fluid with those of an equilibrium fluid with the same one-body density profile.…”
Section: Introductionmentioning
confidence: 99%